PENERAPAN PEMBELAJARAN INKUIRI MODEL ALBERTANTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PADA MATA KULIAH KALKULUS 1 (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis study aims to enhance of students mathematical problem solving ability at Calculus I through application of inquiry learning of albertas model. This research is classroom action research. Subjects were students at Calculus I, amounting to 40 people. Analysis of the data used is the t-test to the data enhancement (N-gain) the ability of mathematical problem solving. The results of this study showed that the average increase (N-gain) the ability of students mathematical problem solving in the first cycle is 0.43 (medium category) and the second cycle is 0.45 (medium category). These results indicate that the application of inquiry learning of albertas model can enhance of students mathematical problem solving ability at Calculus I. Key words: Mathematical problem solving ability, inquiry learning of albertas model, classroom action research, Calculus I.